Al-Fadl bin Dakin and his efforts in the sciences of hadith, the science of ills, as an example (Islamic Sciences Journal, 2024)
ABSTRACTThe science of ills is considered one of the sciences of hadith. In fact, it is the most important science of hadith, as only the diligent scholar, the one who is familiar with the secrets of the hadith and knows the words and meanings it contains, the conditions of its narrators, those among whom are trustworthy and those among them who are weak, and the number of its methods. He was the Imam. Al-Fadl bin Dukain, knowledge of the reasoned hadiths and distinguishing between the authentic ones and the invalid ones, but despite the paucity of what we found of the Imam Al-Fadl bin Dukain, he makes it clear that Abu Naim has a specialty in the science of ills, so how could he not, since he is the sheikh of the great imams who wrote the first books on the science of ills, such as Imam Ahmad. , Yahya bin Ma’in, Abu Hatim Al-Razi, Abu Zar’ah Al-Razi, and other adults.
Keywords: Al-Fadl, Dakin, efforts, hadith, reasons